Implementation of Ralph W. Tyler's Objective Model in Curriculum Development at Linggasari 1 Public Elementary School, Banyumas - Catur Wulandari; Wakhudin Wakhudin (Proceedings Series on Social Sciences & Humanities, 2025)
This study examines the implementation of Ralph W. Tyler's Objective Model in curriculum development at SD Negeri 1 Linggasari Banyumas, with a focus on realizing students who are faithful, achieving, and cultured. Students are generally at lower middle economic level with adequate facilities and infrastructure to support the learning process, both intracurricular, co-curricular, and extracurricular. This study uses a qualitative-descriptive approach with a case study method. The study explores the application of Tyler's principles, for educational purposes, learning experiences, and evaluation into the school curriculum. Data were collected through interviews, observations, and documentation studies. The sample used a purposive sampling technique. Data analysis was carried out through thematic coding to identify patterns and findings. The results of the study indicate that the objective model is effective in aligning learning activities with the school vision, despite obstacles such as limited resources and diverse teacher competencies. This study can identify factors that influence the success of implementing this curriculum, so that further strategies can be formulated for improving and developing education in the future.